Macrophage-derived extracellular vesicles as new players in chronic non-communicable diseases - Fengjuan Lin; Huiyu Luo; Jiexian Wang; Qing Li; Longying Zha (Frontiers in Immunology)
Macrophages are innate immune cells present in all tissues and play an important role in almost all aspects of the biology of living organisms. Extracellular vesicles (EVs) are released by cells and transport their contents (micro RNAs, mRNA, proteins, and long noncoding RNAs) to nearby or distant cells for cell-to-cell communication. Numerous studies have shown that macrophage-derived extracellular vesicles (M-EVs) and their contents play an important role in a variety of diseases and show great potential as biomarkers, therapeutics, and drug delivery vehicles for diseases. This article reviews the biological functions and mechanisms of M-EVs and their contents in chronic non-communicable diseases such as cardiovascular diseases, metabolic diseases, cancer, inflammatory diseases and bone-related diseases. In addition, the potential application of M-EVs as drug delivery systems for various diseases have been summarized.